1994
DOI: 10.1677/joe.0.1420085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a polyclonal antiserum to rat growth hormone on circulating insulin-like growth factor (IGF)-I and IGF-binding protein concentrations and the growth of muscle and bone

Abstract: A polyclonal antiserum to rat GH (anti-rGH) injected into rats for 3 or 8 weeks markedly reduced the weight, total protein and RNA content of muscles of the hind limb. These effects were prevented when bovine GH (bGH) was administered simultaneously. In a second experiment, the effects of 8 weeks of treatment with anti-rGH on the growth of the whole body, muscle and bone were investigated. Body weights of rats were decreased by 58% by treatment with anti-rGH; muscle weights were reduced by slightly more than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…17 Oestrogen deficiency also downregulates the transcription of the gene for insulin-like growth factor 1, reducing bone formation as a result. 18 Various intermediary pathways have been found that participate in the oestrogen-mediated biological responses of osteoblasts, such as transforming growth factor (TGF)-β, the Wnt signalling pathways and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…17 Oestrogen deficiency also downregulates the transcription of the gene for insulin-like growth factor 1, reducing bone formation as a result. 18 Various intermediary pathways have been found that participate in the oestrogen-mediated biological responses of osteoblasts, such as transforming growth factor (TGF)-β, the Wnt signalling pathways and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines were determined to have strong action on bone absorbing and restrain bone forming (Cohen-Solal et al, 1998;Cohen-Solal et al, 1993;Cheleuitte et al, 1998). The estrogen deficiency also down-regulated the gene transcription level of insulin like growth factor (IGF1) following reduced bone forming (Palmer et al, 1994). Furthermore, osteoporosis has been found to be under the control of a large number of genes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the concentration of IGFBP-4 in serum of rats doubled after treatment with bGH (38). As IGFBP-4 is known to inhibit actions of IGFs (for review, see Ref.…”
Section: Figurementioning
confidence: 99%
“…After weaning at 3 weeks of age, the animals were fed a standard rodent diet (Altromin 1324; Altromin, Lage, Germany: 185.5 g protein, 535.6 g disaccharide, 38.0 g fat, 590 kJ convertible energy per kg). During week 14, a diet high in protein and low in carbohydrates (Altromin 1001; 547.2 g protein, 6.7 g disaccharide, 111.6 g fat, 753 kJ convertible energy per kg) was fed to stimulate PEPCK promoter-controlled transgene expression.…”
Section: Generation Of Transgenic Mice and Animal Husbandrymentioning
confidence: 99%